Perspectives on the Training of Chinese Primary Health Care Physicians to Reduce Chronic Illnesses and Their Burden - Sun, Wenmin; Li, Yang; Hu, Yiting; Rao, Xin; Xu, Xingzhi; Browning, Colette Joy; Thomas, Shane Andrew (Frontiers in Public Health, 2019)
This paper is a commentary on the training of Chinese Primary Health Care Doctors to reduce chronic illness and its burden. First, we will consider the policy position of the Chinese government concerning the development of a competent and enlarged primary physician workforce to deliver the proposed primary health care system reforms. We then turn to a review of the drivers of the high burden of chronic illnesses especially in older people in China. We argue that the curriculum for the training of primary health care medical practitioners should match the demonstrated high prevalence chronic illnesses and their risk factors and that there needs to specific competencies in prevention and mitigation of the diseases and their risk factors.